A review of wearable antenna - Rais, N.H.M.; Soh, Ping Jack; Fareq, Malek; Ahmad, S.; Nur Baya, Mohd Hashim; Hall, Peter S. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/